PENGARUH EFFLEURAGE MASSAGE DENGAN VIRGIN COCONUT OIL UNTUK MENCEGAH LUKA TEKAN PADA PASIEN IMOBILISASI - Wahidin, Alisha Qortrunnada M, Ahmad Muzaki (Jurnal Ilmiah Keperawatan, 2022)
Immobilization is the inability to move freely due to a therapeutic condition that is directly related to internal factors such as chronic disease or health status. Pressure sores are injuries to the skin and/or underlying tissue which are usually caused by bony prominences and pressure or a combination of pressure and friction. Effleurage massage is rubbing parts of the body by using movements of the entire surface of the palms, fingers and palms to adjust the body parts being rubbed. Virgin coconut oil is pure coconut oil produced from processing coconut flesh without heating and has many benefits, one of which is supporting tissue repair and healing. Knowing the effect of effleurage massage with virgin coconut oil to prevent pressure sores in immobilized patients. This type of research uses the literature review method by outlining theories, findings, and research materials from several researchers which are used as the basis for conducting literature studies. Article searches were carried out using Google Scholar published from 2016 to 2020 which were accessed in full text in pdf format. Based on the five articles that have been presented by the author, it shows that effleurage massage with virgin coconut oil is effective in preventing pressure sores in immobilized patients.